Oligocene-Miocene ramp system (Asmari Formation) in the NW of the Zagros basin, Iran: Microfacies, paleoenvironment and depositional sequence - Hossein Vaziri-Moghaddam; Ali Seyrafian; Azizolah Taheri; Homayoon Motiei (Revista Mexicana de Ciencias Geológicas)
The Asmari Formation deposited in the Zagros foreland basin during the Oligocene-Miocene. Four different measured sections were studied in this area in order to interpret the facies, depositional environment and sequence stratigraphy of the Asmari Formation. In this study, thirteen different microfacies types have been recognized, which can be grouped into six depositional environments: tidal flat, restricted lagoon, open lagoon, shoal, slope and basin. The Asmari Formation represents sedimentation on a carbonate ramp. Four third-order sequences are identified, on the basis of deepening and shallowing patterns in the microfacies and the distribution of the Oligocene-Miocene foraminifers. The depositional sequences 1, 2 and 3 were observed in Dehluran and Kabirkuh-Darrehshahr areas, and are synchronous with a period of either erosion or non-deposition represented by unconformities in Mamulan and Sepid Dasht areas.